Reducing Depression in Adolescents Through Art Media Using Single Subject Research (SSR): - - Nur Shokhiyah S.Ag., M.Si., Nunuk (TEXTURE Art and Culture Journal, 2025)
This study aims to find out how painting therapy can reduce the level of depression in adolescents. This study used an experimental method with a Single Subject Research (SSR) design. The research subjects were teenagers who experienced depression. This study uses an A-B-A design. This design can show a causal relationship between the independent variable and the dependent variable. The results of the study showed that the score and the average level of depression in adolescents with painting interventions decreased depression. The average value of the depression level at Baseline-1 (A-1) is 66.7%. At the Intervention stage (B) it decreased to (40%), then it decreased again at the Baseline-2 (A-2) stage, namely to (26.7%). This study proves that painting can reduce depression in adolescents, then behavioral observations are carried out, that adolescents are able to express the problems they face through painting activities. Painting also trains teenagers to grow their self-confidence, because teenagers are given the freedom to express what they want without feeling burdened.